1996
DOI: 10.1289/ehp.96104s3553
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and p53 mutations in lung cancer and bladder cancer.

Abstract: We report here a compilation of p53 mutation results from two smoking-related cancers, lung cancer and bladder cancer. The overall mutation frequencies reported for these two types of cancer were relatively similar-50% in lung cancer and 40% in bladder cancer. The compiled data from lung cancer and bladder cancer suggest an increasing proportion of patients with p53 mutations in nonsmokers, former smokers, and current smokers, in that order, in both cancer groups. Taken together, more than half (55% and 56% fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Furthermore, a few studies showed no obvious correlation between the types and/or frequencies of p53 mutations in bladder tumors and the patients' smoking history (52,53). In lines with several previous findings (5,(10)(11)(12)(13)50,54), the majority of p53 mutations in our study were G:C-A:T transitions (62.9%), followed by transversions (34.3%), and occurred throughout exons 4 to 8. Furthermore, eight of the mutations in our study occurred at the same codons as those reported by Stern et al (50), including a CGG-TGG transition at codon 282 and a CGG-CAG transition at codon 248 that were identified in both studies.…”
Section: ------------------------------------------------------------supporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, a few studies showed no obvious correlation between the types and/or frequencies of p53 mutations in bladder tumors and the patients' smoking history (52,53). In lines with several previous findings (5,(10)(11)(12)(13)50,54), the majority of p53 mutations in our study were G:C-A:T transitions (62.9%), followed by transversions (34.3%), and occurred throughout exons 4 to 8. Furthermore, eight of the mutations in our study occurred at the same codons as those reported by Stern et al (50), including a CGG-TGG transition at codon 282 and a CGG-CAG transition at codon 248 that were identified in both studies.…”
Section: ------------------------------------------------------------supporting
confidence: 93%
“…There have been several studies investigating the relationship between polymorphisms of DNA repair genes, specifically XPD and XRCC1 (28,29,(31)(32)(33)(34)(35)46,47), and the role of p53 mutations (10)(11)(12) in bladder cancer. Given the lack of direct functional measures of DNA repair capacity associated with the different polymorphisms, it is difficult to integrate the sometime divergent results of the existing studies on XPD and XRCC1.…”
Section: ------------------------------------------------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…Their potent carcinogenic capability is primarily mediated by imposing genotoxic stress and damage in host cells. For example, formation of DNA adducts is frequently induced, which results in loss-of-function mutation in tumor suppressor genes, such as p53 (39,(45)(46)(47)(48). p53 is a well-established master regulator for the DNA repair response, cell cycle checkpoint and apoptosis, and numerous studies have implicated a long-standing association between the high incidence of its perturbed expression or function and the development of various types of cancer (49,50).…”
Section: Discussionmentioning
confidence: 99%